Targeting Promoter G‐Quadruplex DNAs by Indenopyrimidine‐Based Ligands. Issue 12 (30th October 2014) - Diveshkumar, K. V.; Sakrikar, Saaz; Harikrishna, S.; Dhamodharan, V.; Pradeepkumar, P. I.
Abstract The formation of G‐quadruplex structures can regulate telomerase activity and the expression of oncogenes at the transcriptional and translational levels. Therefore, stabilization of G‐quadruplex DNA structures by small molecules has been recognized as a promising strategy for anticancer drug therapy. One of the major challenges in this field is to impart stabilizing molecules with selectivity toward quadruplex structures over duplex DNAs, and to maintain specificity toward a particular quadruplex topology. Herein we report the synthesis and binding interactions of indenopyrimidine derivatives, endowed with drug‐like properties, with oncogenic promoters of c‐myc and c‐kit, telomeric and duplex DNAs. The results show specific stabilization of promoter over telomeric quadruplexes and duplex DNAs. Molecular modeling studies support the experimental observations by unraveling the dual binding mode of ligands by exploiting the top and bottom quartets of a G‐quadruplex structure. This study underscores the potential of the indenopyrimidine scaffold, which can be used to achieve specific G‐quadruplex‐mediated anticancer activity.